The Efficacy and Safety of Myo-inositol Supplementation for the Prevention of Gestational Diabetes Mellitus in Overweight and Obese Pregnant Women:: A Systematic Review and Meta-Analysis - Factor, Patricia Ann; Corpuz, Hannah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Background. Myo-inositol has emerged as one of the preventive therapies for the development of gestational diabetes mellitus in at-risk populations. This systematic review and meta-analysis was conducted to determine the efficacy and safety of myo-inositol in decreasing the incidence of gestational diabetes in overweight and obese pregnant women. Methodology. This meta-analysis was conducted using the standard Cochrane methodology and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 guidelines. Inclusion criteria were randomized controlled trials (RCTs) that enrolled overweight and obese pregnant women and used myo-inositol supplementation. The primary outcome was the incidence of gestational diabetes mellitus at 24-28 weeks. Secondary outcomes included cesarean section rate, the incidence of pregnancy-induced hypertension, macrosomia and preterm delivery. Risk ratios (RRs) and 95% confidence intervals (CIs) were used for dichotomous data. Results. Six RCTs were included. Compared to standard micronutrient supplementation, standard dose of myo-inositol (4 g) may reduce the incidence of GDM (RR 0.54; CI [0.30, 0.96]; n = 887 women), but the certainty of evidence is low to very low. With low-dose myo-inositol however, evidence is uncertain about its benefit on the incidence of gestational diabetes mellitus in overweight and obese women with RR 0.71; CI [0.14, 3.50]. No adverse effects were noted. For the secondary outcomes, standard dose myo-inositol appears to reduce the incidence of pregnancy-induced hypertension and preterm delivery, but the certainty of evidence is low to very low. Conclusion. Current evidence is uncertain on the potential benefit of myo-inositol supplementation in overweight and obese pregnant women. While studies show that 4 g myo-inositol per day may decrease the incidence of GDM, pregnancy-induced hypertension and pre-term birth with no associated risk of serious adverse events, the certainty of evidence is low to very low. Future high-quality trials may provide more compelling evidence to support practice recommendations.